Selenium Dependent Glutathione Peroxidase: A Physiological Regulatory System for Platelet Function - Perona, G; Schiavon, R; Guidi, G C; Veneri, D; Minuz, P (Thrombosis and Haemostasis, 1990)
In human platelets the selenoenzyme glutathione peroxidase (GSH-Px) acts as a scavenger of the peroxides generated during the burst of arachidonic acid (AA) metabolism. Such a mechanism inhibits the biosynthesis of both thromboxane A2 (TXA2) and lipoxygenase products. The same mechanism is not effective on the prostacyclin (PGI2) biosynthesis from cultured endothelial cells. In order to evaluate this effect in vivo, besides in vitro, we activated the enzyme in eight normal volunteers by increasing their daily Se intake for 8 weeks, monitoring: platelet GSH-Px activity, platelet aggregation induced by A A and U 44069, and concurrent malondialdehyde (MDA) and thromboxane B2 (TXB2) production, urinary excretion of renal and systemic TXA2 and PGI2 metabolites, platelet enzyme activities of the hexose monophosphate pathway and glutathione content, platelet adenine nucleotides, bleeding time, plasma Se concentration. We found: a) progressive platelet GSH-Px activation by Se paralleling an enhancement of platelet aggregation threshold values for AA, but not for U 44069; b) concurrent inhibition of platelet biosynthesis of TXA2 both in vitro and in vivo while the biosynthesis of systemic prostacyclin was unaffected; c) a progressive increase in the bleeding time, unmodified by aspirin. In conclusion, we believe that Se-dependent GSH-Px represents a physiological mechanism regulating the biosynthesis of prostanoids with implications in platelet function and that a Se dietary supplement might be considered in the prevention of arterial thrombosis.